Development of Bikipasi (Bianglala kisah panggung sinaran) as a learning medium sunday school Buddha Dharma Santi East Lampung - Tri Lestari; Komang Sutawan; Susanto Susanto (International Journal of Science and Applied Science: Conference Series, 2025)
This study focuses on the development and feasibility testing of BIKIPASI (Bianglala Kisah Panggung Sinaran) as a non-digital educational medium designed to overcome the limitations of attractive learning media at the Dharma Santi Buddhist Sunday School, East Lampung. Using a Research and Development (R&D) approach based on the modified Borg and Gall model, this study followed seven systematic stages to ensure a focused product design and evaluation process. The research subjects were Majjhima Sekha level students, with data collection methods including observation, interviews, expert validation questionnaires, and pretest and posttest tests. These instruments were used to measure the effect of using BIKIPASI on students' understanding of character building themes, particularly the values of honesty and humility. This media has undergone validation by media experts and subject matter experts, obtaining feasibility scores of 98% and 82%, respectively, indicating that BIKIPASI is highly suitable for use. Statistical analysis using a paired sample t-test showed a significant increase in learning outcomes after using this media (p-value < 0.05). These findings confirm that BIKIPASI is capable of improving students' understanding of moral values in a non-digital learning environment. Given the limited access to digital technology in rural areas, BIKIPASI is a practical and culturally responsive alternative. In addition, the flexibility of topics that can be raised makes it an effective tool for educators in implementing active and meaningful learning. This innovation supports a more inclusive and interactive character education, especially in areas that are not yet fully accessible by digital technology.